Clinical outcome of root caries restorations using ART and rotary techniques in institutionalized elders - Alberto Carlos CRUZ GONZALEZ; Dairo Javier MARÍN ZULUAGA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to compare the clinical performance of root caries restorations after a six-month period using two methods, a conventional technique with rotary instruments and an atraumatic restorative technique (ART), in an institutionalized elderly population in the city of Bogotá, Colombia. Root caries represents a multifactorial, progressive, chronic lesion with softened, irregular and darkened tissue involving the radicular surface; it is highly prevalent in the elderly, especially in those who are physically or cognitively impaired. A quasi-experimental, double-blind, longitudinal study was carried out after cluster randomization of the sample. Two different experienced dentists, previously trained, performed the restorations using each technique. After six months, two new investigators performed a blind evaluation of the condition of the restorations. The results showed a significantly higher rate of success (92.9%) using the conventional technique (p < 0.03). However, we concluded that ART may have been the preferred technique in the study population because 81% of those restorations survived or were successful during the observation period.